Eksistensi Undang-undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik Dalam Perspektif Politik Hukum - Uswatun Hasanah (Fakultas Hukum Universitas Mulawarman, 2009)
Undang-undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik had extended the interpretation of its principles and norms, because cyber space can be categorized as a concrete legal act although basically it has virtual character. This act had also extended the interpretation of burden system. In activities of electronic transaction, it recognizes the use of electronic document which has equal status with the ordinary document. Undang-undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik had extended the jurisdiction of the application of national law against electronic transaction